Arctic plants are capable of sustained responses to long-term warming. Issue 1 (1st January 2016) - Barrett, Robert T.; Hollister, Robert D.
Abstract : Previous studies have shown that Arctic plants typically respond to warming with increased growth and reproductive effort and accelerated phenology, and that the magnitude of these responses is likely to change over time. We investigated the effects of long-term experimental warming on plant growth (leaf length) and reproduction (inflorescence height, reproductive phenology and reproductive effort) using 17–19 years of measurements collected as part of the International Tundra Experiment (ITEX) at sites near Barrow and Atqasuk, Alaska. During the study period, linear regressions indicated non-significant tendencies towards warming air temperatures at our study sites. Results of our meta-analyses on the effect size of experimental warming (calculated as Hedges' d ) indicated species generally responded to warming by increasing inflorescence height, increasing leaf length and flowering earlier, while reproductive effort did not respond consistently. Using weighted least-squares regressions on effect sizes, we found a significant trend towards dampened response to experimental warming over time for reproductive phenology. This tendency was consistent, though non-significant, across all traits. A separate analysis revealed significant trends towards reduced responses to experimental warming during warmer summers for all traits. We therefore propose that tendencies towards dampened plant responses to experimental warming over time are the result of regional warming. These results show that Arctic plants are capable of sustained responses to warming over long periods of time but also suggest that, as the region continues to warm, factors such as nutrient availability, competition and herbivory will become more limiting to plant growth and reproduction than temperature.